Dynamics and synchronization control in schizophrenia for EEG signals. (January 2022) - Yao, Rong; Xue, Jiayue; Li, Haifang; Wang, Qianshan; Deng, Hongxia; Tan, Shuping
Highlights: Brain network is controllable but is not easily controllable. The network synchronization was significantly higher in schizophrenia. Brain network topology differences dictate distinct in controlling the trajectories. Abstract: Cognitive dysfunction may be central to neurocognitive deficits in schizophrenia. To further explore brain network dynamics and synchronization in first-episode schizophrenia, we exploited pinning control theory to adjust and control the brain regions interacting with each other in schizophrenia to make their network synchronization stability consistent with that of healthy individuals. Our results revealed that in a short-term memory task, the right frontal lobe was abnormal in schizophrenia, resulting in higher synchronous oscillation behavior of the entire brain networks compared with the healthy participants. And the synchronization was positively correlated with each participant's response time (RT) and negatively correlated with their response accuracy (ACC). In the healthy participants, the frontal lobe facilitated a higher brain synchronization state, whereas in the schizophrenia patients, the parietal-occipital lobe facilitated a higher brain synchronization state. These data provide new evidence for task-relevant dynamic interactions between brain regions in schizophrenia and provide theoretical methods for the adjustment and control of brain networks.